Clinical application and early outcomes of the aortouni-iliac configuration for endovascular aneurysm repair - Kiguchi, Misaki M.; Böckler, Dittmar (Journal of vascular surgery, 2014)
Objective - The objective of this study was to review the current anatomic indications for and early results of aortouni-iliac (AUI) devices for endovascular aneurysm repair. - Methods - A total of 128 patients receiving an Endurant (Medtronic Inc, Minneapolis, Minn) AUI device in the U.S. Investigational Device Exemption trial (44 patients) or the Endurant Stent Graft Natural Selection Global Postmarket Registry (84 patients) were reviewed. Preoperative computed tomography imaging of patients in the Investigational Device Exemption trial and case report forms of Registry patients were used to determine anatomic indications. Baseline characteristics and early results were compared with those of 1305 patients receiving a bifurcated (BIF) device in sister studies. - Results - The indication for the AUI device was unclear from case report forms in two Registry cases. The remaining 126 patients had a unilateral iliac occlusion in 30 (23%), a severely narrowed aortic segment in 58 (45%), severe iliac occlusive disease in 28 (22%), severe iliac tortuosity in 29 (23%), or complex iliac aneurysms in 19 (15%). Two patients had a previous aortobifemoral graft; 38 patients (30%) had multiple indications. The AUI cohort included more women than the BIF group did (19% vs 10%; P < .01) and had more severe comorbidities. Successful deployment was achieved in all AUI cases. The 30-day mortality was 2% (BIF cohort, 1%; P = .21). More AUI patients underwent repair under general anesthesia (81% vs 64%; P < .01), and procedures were longer (110.9 ± 54.9 minutes vs 99.2 ± 44.3 minutes; P = .02). Except for longer intensive care unit stays (19.6 ± 80.0 hours vs 9.0 ± 34.8 hours; P = .01) and higher myocardial infarction rates (4% vs 1%; P < .01), outcomes of the AUI cohort were similar to those of the BIF cohort. There were no migrations, ruptures, fractures, or open conversions at up to 1-year follow-up. - Conclusions - The AUI configuration extends endovascular aneurysm repair feasibility to several hostile anatomic conditions. Despite increased comorbidities in the recipient patient population and associated higher rates of postoperative myocardial infarction and respiratory complications, early outcomes with the new generation of AUI devices are acceptable and comparable to those after treatment with BIF configurations.